2022
DOI: 10.1107/s1600577521013473
|View full text |Cite
|
Sign up to set email alerts
|

From EXAFS of reference compounds to U(VI) speciation in contaminated environments

Abstract: Understanding the speciation of technogenic uranium in natural systems is crucial for estimating U migration and bioavailability and for developing remediation strategies for contaminated territories. Reference EXAFS data of model laboratory-prepared uranium compounds (`standards') are necessary to analyze U-contaminated samples from nuclear legacy sites. To minimize errors associated with measurements on different synchrotrons, it is important not only to compare data obtained on environmentally contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…It should be noted that the Debye-Waller parameter increases with the increase of oxides defectiveness, which is a natural consequence of structure disordering as the number of defects increases. The distance to U coordination sphere is the same for all oxides of the series and coincides with the value known for the stoichiometric UO 2 (3.87 ± 0.01 Å) from earlier EXAFS calculations 60 . A shift of 0.01 Å appears only in UO 2.20 .…”
Section: Xanes and Exafs For Characterization Of Synthetized Uranium ...supporting
confidence: 86%
“…It should be noted that the Debye-Waller parameter increases with the increase of oxides defectiveness, which is a natural consequence of structure disordering as the number of defects increases. The distance to U coordination sphere is the same for all oxides of the series and coincides with the value known for the stoichiometric UO 2 (3.87 ± 0.01 Å) from earlier EXAFS calculations 60 . A shift of 0.01 Å appears only in UO 2.20 .…”
Section: Xanes and Exafs For Characterization Of Synthetized Uranium ...supporting
confidence: 86%
“…As shown in Figure 4A, a similar set of spectral lines is observed for these compounds; this is consistent with related local structures. The Raman spectrum of (NH 4 )[NpO 2 CO 3 ] can be divided into three parts: low-frequency region up to 200 cm −1 , containing bending vibrations of NpO 2 + and CO 3 2− ; stretching vibrations of the NpO 2 + cation at 766 cm −1 [31,32], and peaks of CO 3 2− bending and stretching vibrations at 718 and 1071 cm −1 , respectively [33]. The positions of the peaks of the carbonate group vibrations are consistent with those in ammonium uranyl carbonate and are within the characteristic range of the carbonate ion vibrations [34].…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…[9][10][11][12] Also, uranium speciation in natural waters and in the environment has been studied by various methods, including anion exchange, laser spectroscopy, X-ray absorption spectroscopy, and Raman spectroscopy. [13][14][15][16][17] Most of those studies were in equilibrium and do not include dynamic reaction processes. As the deposition of U includes changes in the oxidation state nanoparticulation following reduction, it was reported that the reduction of U VI to U IV by Fe II and green rust leads to the formation of U IV O 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%